STRATEGI PEMBANGUNAN SISTEM PENGOLAHAN AIR LIMBAH DOMESTIK TERPUSAT (SPALD-T) DIKAMPUNG SELUMIT PANTAI - denny indrawanto denny; Selly Ratna Sari (Clarias : Jurnal Perikanan Air Tawar, 2023)
The condition of wastewater treatment infrastructure is very minimal in the city of Tarakan, aiming to develop a strategy for managing domestic wastewater infrastructure in the city of Tarakan with reference to the MDGs targets, namely up to 2015-2019 and the 2030 Sustainable Development Goals (SDG's) achieving access to black water wastewater safe, while for gray water it can be in the form of an integrated domestic wastewater management strategy and program in increasing population access to safe black water and gray water treatment by providing individual septic tanks, communal septic tanks, and anaerobic partition reactor WWTPs.It is hoped that increasing institutional capacity and active participation of the community will improve domestic wastewater management so that it can improve the health status of the people of Tarakan City and reduce the rate of environmental damage.